Changes in medication use in a cohort of patients with advanced cancer: The international multicentre prospective European Palliative Care Cancer Symptom study. (April 2018) - Paque, Kristel; Elseviers, Monique; Vander Stichele, Robert; Pardon, Koen; Hjermstad, Marianne J; Kaasa, Stein; Dilles, Tinne; De Laat, Martine; Van Belle, Simon; Christiaens, Thierry; Deliens, Luc
Background: Information on medication use in the last months of life is limited. Aim: To describe which medications are prescribed and deprescribed in advanced cancer patients receiving palliative care in relation to time before death and to explore associations with demographic variables. Design: Prospective study, using case report forms for monthly data collection. Medication included cancer treatment and 19 therapeutic groups, grouped into four categories for: (1) cancer therapy, (2) specific cancer-related symptom relief, (3) other symptom relief and (4) long-term prevention. Data were analysed retrospectively using death as the index date. We compared medication use at 5, 4, 3, 2 and 1 month(s) before death by constructing five cross-sectional subsamples with medication use during that month. Paired analyses were done on a subsample of patients with at least two assessments before death. Setting/participants: We studied the medication use of 720 patients (mean age 67, 56% male) in 30 cancer centres representing 12 countries. Results: From 5 to 1 month(s) before death, cancer therapy decreased (55%–24%), most medications for symptom relief increased, for example, opioids (62%–81%) and sedatives (35%–46%), but medication for long-term prevention decreased (38%–27%). The prevalence of chemotherapy was 15.5% in the last month of life, with 9% of new courses started in the last 2 months. With higher age, chemotherapy and opioid use decreased. Conclusion: Medications for symptom relief increased in almost all medication groups. Deprescribing was found in heart medication/anti-hypertensives and cancer therapy, although use of the latter remained relatively high.